A low‐cost multimodal head‐mounted display system for neuroendoscopic surgery. Issue 1 (14th December 2017) - Xu, Xinghua; Zheng, Yi; Yao, Shujing; Sun, Guochen; Xu, Bainan; Chen, Xiaolei
Abstract: Background: With rapid advances in technology, wearable devices as head‐mounted display (HMD) have been adopted for various uses in medical science, ranging from simply aiding in fitness to assisting surgery. We aimed to investigate the feasibility and practicability of a low‐cost multimodal HMD system in neuroendoscopic surgery. Methods: A multimodal HMD system, mainly consisted of a HMD with two built‐in displays, an action camera, and a laptop computer displaying reconstructed medical images, was developed to assist neuroendoscopic surgery. With this intensively integrated system, the neurosurgeon could freely switch between endoscopic image, three‐dimensional (3D) reconstructed virtual endoscopy images, and surrounding environment images. Using a leap motion controller, the neurosurgeon could adjust or rotate the 3D virtual endoscopic images at a distance to better understand the positional relation between lesions and normal tissues at will. Results: A total of 21 consecutive patients with ventricular system diseases underwent neuroendoscopic surgery with the aid of this system. All operations were accomplished successfully, and no system‐related complications occurred. The HMD was comfortable to wear and easy to operate. Screen resolution of the HMD was high enough for the neurosurgeon to operate carefully. With the system, the neurosurgeon might get a better comprehension on lesions by freely switching among images of different modalities. The system had a steep learning curve, which meant a quick increment of skill with it. Compared with commercially available surgical assistant instruments, this system was relatively low‐cost. Conclusions: The multimodal HMD system is feasible, practical, helpful, and relatively cost efficient in neuroendoscopic surgery. Abstract : Multimodal head‐mounted display, neuroendoscopic surgery.